Conocimiento del personal de enfermería y la calidad del cuidado neonatal en el IESS - Loja. - Román Lapo, Angela Dalila (2013)
The Hospital Manuel Ygnacio Monteros the Social Security Institute, is a secondary hospital that provides health care to the population affiliated to the province of Zamora Chinchipe top of Loja and El Oro, has Neonatology service that provides care normal newborns with different pathologies. The research aimed to determine the level of knowledge possessed by the staff of Maternal Child Nursing IESS Area Loja, expressed in the quality of care offered to the newborn (NB) and normal hospital, in order to help standardize procedures for quality of care, through participation in the development of specific nursing protocols. We performed a cross-sectional study and design of field with focus on comprehensive and quantitative - qualitative methodologies. The sample universe consisted of 28 professional nurse. As for the techniques used are applied : an interview aimed at each of the heads of the service, based on a guide and also used a survey of nursing staff to determine their level of knowledge and a survey of the families of Newborns hospitalized for important information on the quality of nursing care . The results showed that the level of knowledge possessed by the nursing staff on the quality of care they should receive the neonate the area Maternal - Child is excellent, since 100 % of staff applies Nursing care plans for each newborn, and 100 % of nurses biosafety rules apply, as to 78.57 % think that the staff is sufficient to meet the demand of patients, we also determined that the area Maternal - Child has sufficient material resources. This area is implementing the Baby Friendly Hospital Program, which promotes the rooming-in and breastfeeding early; this is intended to improve the quality of care provided. As a result unify criteria recommended by the professionals about responsibility and ethics in care and strengthen the / the Nurse / as and other industry professionals, knowledge through research on comprehensive care to neonate. Finally, 66.67% of users believe that the information provided by the nursing staff meets their concerns and 66.67% Nursing care qualify as great.